Influence of service quality and role of value for money towards customer satisfaction of Air Asia Airlines / Fatin Nur Atiqah Mohamad Aswad - Mohamad Aswad, Fatin Nur Atiqah (Faculty of Business and Management, 2019)
The quality of service is described as a function of the distinction between the estimated service and the perception of the real service given to the customer while value for money helps as a predictable element used by marketers and evolve promotion and pricing strategies. As for customer satisfaction, customer will instantly repeat their purchase when they are satisfied with the product and service that offered by the firm. “Influence of Service Quality and Role of Value for Money Towards Customer Satisfaction of Air Asia Airlines”. The purpose of this research is to study the service quality elements (tangible, reliability, responsiveness, assurance and empathy) towards satisfaction of AirAsia Airline customers. Main problem that AirAsia Airline faced are too many complaints from customers, delay in flight schedule and cancellation, lastly, decreasing in customer satisfaction. The main objective of this research is to identify the relationship between service quality elements and value of money towards satisfaction of Air Asia Airlines passengers. For research methodology, six hypotheses were constructed to determine the relationship between service quality elements (tangible, reliability, responsiveness, assurance, and empathy) towards customer satisfaction. The questionnaires were distributed and 105 respondents were obtained with convenience sampling will used as sampling technique that was analyzed with Statistical Program for the Social Science (SPSS) version 23. Result showed that value of money has the relationship with AirAsia Airlines’s passenger satisfaction, while service quality elements (tangible, reliability, responsiveness, assurance, empathy) did not have relationship with AirAsia Airlines’ passenger satisfaction.